Green-HIT: A Holistic IoT System for Forest Monitoring and Management - Pamboris, Andreas; Iasonos, Iasonas; Kyriakou, Nikolas; Prodromou, Maria; Cheng, Pericles; Konstantinidis, Andreas (My University, 2025)
Abstract. Forests play a critical role in climate regulation, biodiversity preservation, and ecosystem sustainability, making their protection and effective management a strategic priority under the European Green Deal. Green-HIT is a holistic IoT system designed to transform forest management and monitoring through the integration of advanced technologies, namely, edge computing, AIdriven analytics, cutting-edge Unmanned Aerial Vehicle (UAV) technologies, and an interoperable data infrastructure. It addresses key challenges faced by forest authorities and environmental stakeholders by enabling real-time monitoring, intelligent decision-making, and automated response mechanisms. Green-HIT incorporates a range of modules to support prevention, early detection and reaction to forest Fires, deforestation detection and reforestation planning, illegal activity detection, and forest mapping, using Field and remote sensing
Keywords: Forests; Biodiversity; Ecosystem sustainability; Forest management